P.188 Neurotrauma in Indigenous populations of Canada: challenges and future directions: A Scoping Review. (November 2021) - Salaheen, Z; Moghaddamjou, A; Fehlings, MG
Abstract : Background: Neurotrauma accounts for over 24 000 hospitalizations annually in Canada. Among those affected, Indigenous peoples are disproportionately impacted. The goal of this scoping review is to identify factors underlying these disparities. Methods: A scoping review was conducted to collect papers pertaining to neurotrauma in Indigenous populations of Canada. Using MEDLINE, 676 articles were screened with MeSH terms including 'Indigenous', 'spinal cord injuries', 'brain injuries, traumatic' and 'Canada' as of April 2021. Results: Studies report over twice the incidence of traumatic brain injury and traumatic spinal cord injury in Indigenous populations compared to non-Indigenous populations. The burden of neurotrauma is attributable to infrastructure disparities in rural communities and reserves, elevated rates of substance use and violence, and inequities in treatment and rehabilitation following injury. These issues are deeply rooted in the trauma endured by Indigenous peoples through the course of Canadian history, owing to government policies that severely impacted their socioeconomic conditions, culture, and access to healthcare services. Conclusions: Systems-level interventions guided by Indigenous community members will help to address the disparities that Indigenous peoples face in the care and rehabilitation of neurotrauma. This study will inform further research of culturally appropriate approaches to reduce neurotrauma burden among Indigenous peoples.